Experimental Evaluation of Tool Geometries for the Ultrasonic Crimping Process for Tubular Cable Lugs - Seefried, Johannes; Gläßel, Tobias; Kühl, Alexander; Mayr, Andreas; Franke, Jörg (2019 IEEE Holm Conference on Electrical Contacts, 2019)
In the production chain of electric drives, the electrical and mechanical contacting of the winding ends with a contact element is a time-consuming and cost-intensive process step. The most common processes, e.g., hot crimping, are characterized by high tool wear and enormous energy consumption. An innovative and at the same time energy- efficient process is the ultrasonic crimping process which also combines the two process steps of skinning and contacting in a single process. The thermal energy required for skinning is based on the damping of oscillation energy in the cable lugs used. Due to the direct heat generation in the cable lug and the oscillations coupled in, the process has high potentials with regard to process stability, contacting of high-frequency litz wires and energy consumption. However, some disadvantages like the occasional occurrence of fatigue fractures in the tubular cable lugs and unclear dependencies reducing process reliability have to be investigated. One possibility to avoid the cracks and to further increase the process stability of ultrasonic crimping is the evaluation of adapted tool geometries. In the context of this paper, different sonotrode and anvil geometries are compared and evaluated with regard to electrical, mechanical and visual connection quality.<br